VARIASI MORFOLOGI PANDANUS POLYCEPHALUS LAM. DI KEBUN RAYA BOGOR - Yunita Nur Nur; Rugayah Rugayah (PTTI, 2012)
Pandanus polycephalus described firstly by Lamarck in 1785, Warburg in 1900 further described P. polycephalus based on P. humilis of Rumphius (1743) and P. humilis of Lour. (1790). Several previous descriptions of the species showed variation on the number of cephalia in one infructescences, 3–8 cephalia, 4–6 cephalia and 5–8 cephalia. Recent observation on the living collection of Bogor Botanic Garden shows the existence of 3 variations where first variant has lamina and leaf sheath on the terminal, infructescences terminal, number of cephalia 6–8 in one infructescence, bracts greenish white, the second variant has disperse leaves, infrustescences mostly lateral, number of cephalia 4–7 in one infructescences, bract greenish orange, whereas the third variant has intermediate character between the other two, it has spiny stem, disperse leaves, terminal infructescences, 5–8 of cephalia, outer bract greenish white, inner once greenish orange. In Indonesia, P. polycephalus Lam. is distributed in Java, Sumatra, Sulawesi, Moluccas, New Guinea and Papua.